2010
DOI: 10.15517/rbt.v59i4.3426
|View full text |Cite
|
Sign up to set email alerts
|

Ground-foraging ants (Hymenoptera: Formicidae) and rainfall effect on pitfall trapping in a deciduous thorn woodland (Caatinga), Northeastern Brazil

Abstract: The semi-arid Caatinga is the fourth largest biome of Brazil, which biota still remains one of the most poorly known, especially with regard to invertebrate groups. In this study, a ground-foraging ant assemblage was surveyed during one year and the effect of rainfall on pitfall trapping was assessed. The study was performed in an area located in the municipality of Pentecoste (3º48' S-39º20' W), in the State of Ceará. A 200m transect with 20 equidistant sampling points was established. Transect sampling was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…The activity of the terrestrial arthropods as documented by the captures in the pitfall traps did not vary with the amount of rainfall. This is in stark contrast to observations of Nunes et al (2011) and Delsinne et al (2008), where ant numbers in semi-arid areas (Brazilian Caatinga and Paraguayan Chaco, respectively) were drastically reduced by rainfall. However, this could be expected, as our study area is part of the Chocó biogeographic region with rainfall records of up to 12,000 mm.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The activity of the terrestrial arthropods as documented by the captures in the pitfall traps did not vary with the amount of rainfall. This is in stark contrast to observations of Nunes et al (2011) and Delsinne et al (2008), where ant numbers in semi-arid areas (Brazilian Caatinga and Paraguayan Chaco, respectively) were drastically reduced by rainfall. However, this could be expected, as our study area is part of the Chocó biogeographic region with rainfall records of up to 12,000 mm.…”
Section: Discussioncontrasting
confidence: 99%
“…In the same study, Ectatomma quadridens (F. 1793) is mentioned as a predator of S. valida. In Colombia, E. ruidum has also been associated with predation of spittle bugs in pastures, insect pests of citrus (Abadia Lozano et al 2013) and various pests of coffee (Mera Velasco et al 2010). Velázquez et al (2006) identified E. ruidum among the important predators of the agave weevil, Scyphophorus acupunctatus Gyllenhal, 1838 (Coleoptera: Curculionidae) in Venezuela with presence in almost all the sampled areas.…”
Section: Discussionmentioning
confidence: 99%
“…The other species that were found in the four samples had highest abundance in the months of rainy season (January and October). This results may be related to the foraging strategy of each species (PORTER;TSCHINKEL, 1987), to the physical barrier imposed by rain, to the efficiency of the pitfall trap during the rainy months, and to the variation of available resources (NUNES et al, 2011). According to Dos Santos et al, (2012), in the Cerrado biome, during the months with lowest precipitation, the availability and quality of food fall sharply, influencing populations directly, including some ant species (see COGNI;OLIVEIRA, 2004;YAMAMOTO;DEL-CLARO 2008).…”
Section: Discussionmentioning
confidence: 99%
“…ribifolia ), we assessed the online SpeciesLink database (available at http://www.splink.org.br/). To access the occurrence points of D. quadriceps , we searched for papers in the Scopus and Web of Science online database in which we could gather georeferenciated information about sites in which this species was collected (Santana‐Reis & Santos ; Vasconcellos et al ; Quinet & Tavares ; Araújo & Rodrigues ; Nunes et al ; Santos et al ,, ; Medeiros et al ; Nascimento et al ; Cologna et al ; Ulysséa & Brandão ; Lenhart ; Torres et al ; Leal et al ,b). For D. quadriceps , we have only selected occurrence points located in Caatinga vegetation because the selected plant species are strictly associated to this ecosystem (Fig.…”
Section: Methodsmentioning
confidence: 99%